2001
DOI: 10.1038/sj.gene.6363791
|View full text |Cite
|
Sign up to set email alerts
|

IFNs activate toll-like receptor gene expression in viral infections

Abstract: Toll-like receptors (TLRs) mediate innate immune responses to microbes. TLR2, TLR5, TLR6, and TLR9 have been implicated in responses to bacterial components, and TLR4 is the receptor for Gram-negative bacteria. Recently, TLR4 was described to function in respiratory syncytial virus-induced NF-kappaB activation. Here we have analyzed TLR1-9 mRNA expression in human primary macrophages infected with influenza A and Sendai viruses. TLR1, TLR2, TLR4, TLR6, and TLR8 mRNAs were expressed at basal levels in macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
182
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(197 citation statements)
references
References 53 publications
8
182
0
3
Order By: Relevance
“…It will be interesting to study whether the TLR7 sensitivity of other immune cell subsets such as myeloid cells also depends on PDC-derived type I IFN. Of note, type I IFNs were shown to induce TLR7 in macrophages (45), and only myeloid dendritic cells generated in the presence but not in the absence of IFN-␣ were reported to express TLR7 (46).…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to study whether the TLR7 sensitivity of other immune cell subsets such as myeloid cells also depends on PDC-derived type I IFN. Of note, type I IFNs were shown to induce TLR7 in macrophages (45), and only myeloid dendritic cells generated in the presence but not in the absence of IFN-␣ were reported to express TLR7 (46).…”
Section: Discussionmentioning
confidence: 99%
“…We were interested in seeing whether epithelial or endothelial cells express these receptors that would enable direct sensing of viral RNA. We have previously shown that IFN-␣ can up-regulate TLR3 and TLR7 gene expression in human macrophages (17). Therefore, we also studied the effects of IFN-␣ and IFN-␤ on TLR expression in epithelial A549 cells and in HUVECs.…”
Section: Tlr3 Tlr7 and Tlr8 Expression And Tlr-stimulated Response mentioning
confidence: 99%
“…Probes for IL-28 and IL-29 were cloned from total cellular RNA obtained from Sendai virus-infected macrophages by RT-PCR using oligonucleotides GTCTCCA CAGGATCCGCAGGCCTT and CAGCCAGGGGGATCCTTTTTTGGG (IL-28), GAAGGCCAGGGATCCCTTGGAAGA and GTGTCAGGTG GATCCAGGGTGGGT (IL-29). The probes for TLR3, TLR7, and TLR8 have been previously described (17). Ethidium bromide staining of rRNA bands was used to ensure equal RNA loading.…”
Section: Rna Isolation and Northern Blot Analysismentioning
confidence: 99%
“…As a result, it would be interesting to explore the molecular etiology of this pathogenic TLR7 overexpression. Ligation of TLR7 by agonists can stimulate TLR7 expression in a feedforward loop 50 , which implies that high TLR7 abundance might be a sign of the natural stimulation of this receptor by ligands present in the tumor microenvironment. The molecular nature and source of such natural TLR7 agonists remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%